Personality Traits and Social Supports in Adolescents With Persistent Postconcussion Symptoms. Issue 2 (March 2022) - Atif, Hamna; Morgan, Brianne; Tuohy, Kyle; Zukowski, Monica; Foster, Zachary; Loeffert, Andrea; Yeates, Keith O.; Hicks, Steven D.
Abstract : Objectives: To determine whether adolescents with persistent postconcussion symptoms (PPCS) differ from healthy peers in their personality traits and social supports. Setting: Specialty Concussion Clinic and Primary Care Clinic affiliated with an academic medical center. Participants: Ninety-seven adolescents (42 with PPCS, 55 healthy peers; age: 15 ± 2 years). Design: Participants completed a web-based survey that included medical and demographic characteristics, mechanisms of concussion, 10-item Big Five Inventory, and Child and Adolescent Social Support Scale. A Student's 2-tailed t test with multiple testing corrections was used to compare the youths with PPCS to healthy peers. Main Measures: The primary outcome was PPCS, defined by the presence of 2 or more concussion-related symptoms on the Post-Concussion Symptom Scale (PCSS), lasting for more than 4 weeks after initial injury. The secondary outcome was perceived personality traits and social support, based on the 10-item Big Five Inventory and the Child and Adolescent Social Support Scale, respectively. Results: The PPCS group had higher neuroticism scores on their Big Five Inventory than healthy peers. They also reported less social support from teachers and classmates than healthy peers. Conclusion: Youths with PPCS report specific personality and social support characteristics that differ from their peers. These findings suggest that individual personality and school-based social supports may influence concussion recovery.